The teaching, learning and assessment of health advocacy in a South African College of Health Sciences - van Staden, D.; Duma, S. (South African Journal of Higher Education, 2022)
Health advocacy is a core competency identified by Health Professions Council of South Africa to be acquired by health professional graduates. There is a lack of information on how health advocacy (HA) is taught and assessed in health science programmes. The aim of the study was to explore the teaching, learning and assessment of HA in undergraduate health science programmes at a South African university. Methods: Curriculum mapping of eight programmes and a Focus Group Discussion (FGD) with eleven key informants were conducted using a sequential mixed methods approach. Content analysis was used to analyse Curriculum Mapping data. Thematic analysis was used to analyse the FGD data. Results from both data sets were triangulated. Results: Six themes emerged: Perceived importance of HA role for health practitioners; Implicit HA content in curricula; HA as an implicit learning outcome; Teaching HA in a spiral curriculum approach; Authentic Assessment of HA, and Perceived barriers to incorporation of HA into curricula. Conclusion and Recommendations: HA is perceived as an important role for health professionals but it is not explicitly taught and assessed in undergraduate health sciences programmes. Barriers to its teaching and assessment can be addressed through capacity development of academics.